2020
DOI: 10.3389/fimmu.2020.00912
|View full text |Cite
|
Sign up to set email alerts
|

Smad2/4 Signaling Pathway Is Critical for Epidermal Langerhans Cell Repopulation Under Inflammatory Condition but Not Required for Their Homeostasis at Steady State

Abstract: Epidermal Langerhans cells (LCs) are skin-resident dendritic cells that are essential for the induction of skin immunity and tolerance. Transforming growth factor-β 1 (TGFβ1) is a crucial factor for LC maintenance and function. However, the underlying TGFβ1 signaling pathways remain unclear. Our previous research has shown that the TGFβ1/Smad3 signaling pathway does not impact LC homeostasis and maturation. In this study, we generated mice with conditional deletions of either individual Smad2, Smad4, or both S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In the canonical TGFb signaling, TGFb1 binds TGFbR1 and TGFbR2 complex, mediating the phosphorylation of SMAD2 and SMAD3 complex, which forms a heterotrimeric complex with SMAD4 and translocates into the nucleus and regulates TGFb1-targeting genes (Derynck and Zhang, 2003). However, our genetic mouse models with deletion of Smad3 (Xu et al, 2012), Smad2, and Smad4 (Huang et al, 2020) showed no effect of SMAD pathway loss on LCs development at steady state but did show an impact on LC repopulation under inflammatory state. Nevertheless, recent studies revealed that both TGFb family members, TGFb1 and BMP7, can potentially signal through BMPR1A or ALK3 to induce LC differentiation in vitro (Borek et al, 2020;Yasmin et al, 2013), and BMP7-ALK3 signaling leads to the differentiation and proliferation of inflammation-associated LCs from bone marrowederived precursors in psoriatic lesions, which promotes the psoriatic epidermal changes in patients with psoriasis as well as in a psoriatic mouse model (Borek et al, 2020).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…In the canonical TGFb signaling, TGFb1 binds TGFbR1 and TGFbR2 complex, mediating the phosphorylation of SMAD2 and SMAD3 complex, which forms a heterotrimeric complex with SMAD4 and translocates into the nucleus and regulates TGFb1-targeting genes (Derynck and Zhang, 2003). However, our genetic mouse models with deletion of Smad3 (Xu et al, 2012), Smad2, and Smad4 (Huang et al, 2020) showed no effect of SMAD pathway loss on LCs development at steady state but did show an impact on LC repopulation under inflammatory state. Nevertheless, recent studies revealed that both TGFb family members, TGFb1 and BMP7, can potentially signal through BMPR1A or ALK3 to induce LC differentiation in vitro (Borek et al, 2020;Yasmin et al, 2013), and BMP7-ALK3 signaling leads to the differentiation and proliferation of inflammation-associated LCs from bone marrowederived precursors in psoriatic lesions, which promotes the psoriatic epidermal changes in patients with psoriasis as well as in a psoriatic mouse model (Borek et al, 2020).…”
mentioning
confidence: 67%
“…LCs could be derived from bone marrow under inflammatory conditions, and we found that SMAD2 and/or SMAD4 is required for LC repopulation from bone marrow in UVC-treated skin (Huang et al, 2020). To explore the role of ALK3 in LC repopulation, the epidermal LCs (CD45 þ MHCIIhi CD207 hi ) in Csf-1R Cre ALK3 fl/fl and WT littermates were analyzed at 2 weeks after UVC treatment and were found comparable (Figure 1g), indicating that ALK3 is not required for LCs repopulation.…”
mentioning
confidence: 76%
“…In contrast, we found that USP2 inhibits the TGF-β signaling and the proliferation of myeloid cells. In support of this notion, a number of studies have shown that TGFβ signaling promotes the proliferation of myeloid cells ( Bataller et al., 2019 ; Huang et al., 2020 ; Meng et al., 2016 ). Moreover, a recent study has reported that USP2 inhibits TGF-β pathway by promoting deubiquitylation of SMAD7 in glioblastoma cells that has been assumed to originate from glial-type cells and resembles some features of glial macrophages ( Tu et al., 2022 ).…”
Section: Discussionmentioning
confidence: 90%
“…Phagocytosis of apoptotic cells by macrophages and DC leads to inflammatory immune response suppression [12,21]. Transforming growth factor-β1 (TGF-β1) is a fundamental regulator of immune cell development and function and this molecule is a crucial regulatory factor for LC development, maintenance, and function with context-dependent down-stream signaling pathways [22][23][24]. Axl is a TAM (Tyro3, Axl, and Mer) receptor tyrosine kinase family member, which functions as an inhibitor of innate inflammatory responses in dendritic cells and is essential for the prevention of lupus-like autoimmunity [25].…”
Section: Langerhans Cells In Steady State Skin Immune Homeostasismentioning
confidence: 99%
“…The pivotal role of TGF-β in LC development and epidermal residence has been established, in which TGF-β is absolutely required for LC development [113,114], and the activity of TGF-β is dependent on integrins αvβ6 and αvβ8 that are expressed on KC [115,116]. In addition, TGF-β is required for inflammation-induced LC repopulation, in which alternative TGF-β downstream signaling pathways are involved, which is different from steady-state LC maintenance [22,23]. Given the critical role of TGF-β and specific downstream signaling pathways in the epidermal retention and maintenance of LC, as well as the critical involvement of TGF-β in the induction of tolerogenic function in both DC and TRM in multiple tissues, it is tempting to speculate a potential role for TGF-β in programming the LC tolerogenic state.…”
Section: Potential Mechanisms Of Langerhans Cells In Priming Treg Res...mentioning
confidence: 99%